The Influence of Scramble Cooperative Model on Fourth Grader Students’ Learning Achievement on Whole Number Calculation - Monawati Monawati; Alfiati Syafrina; M Yamin; Rahma Fitrah Ulfa (Proceedings of AICS - Social Sciences, 2021)
This research investigates the influence of scramble-type cooperative models onstudents’ learning achievement on whole number calculation material at grade IV classof Elementary School 3 Banda Aceh. This research utilized a quantitative approach of apre-experimental type with a One Group Pretest – Posttest design. This research wasdone at one of primary schools in Banda Aceh, Indonesia, i.e, Sekolah Dasar Negeri 3,specifically grade IV class, in Banda Aceh City. The sample was chosen by usingpurposive sampling from one grade IV class – i.e. Class IV/C, with a total of 32students. The data was collected through a pre-test and a post-test and was analyzedby using the average score, deviation of the pre-test and post-test score, andhypothesis testing using t-test, which is a right-side t-test. The data was analyzed byusing a t-test statistic at the significance rate of α = 0.05. The value of tcount of 19.5was gained from the t-test hypothesis testing from the value of ttable of 1.7, whichmeans that H0 was rejected and H1 was accepted. Therefore, it can be concluded thatthere exists a significant influence of scramble-type cooperative model on students’learning achievement on whole number calculation material at the grade IV class ofElementary School 3 Banda Aceh.Keywords: scramble-type cooperative model, learning achievement, wholenumber calculation operation.